Effectiveness of different methods of health education: A comparative assessment in a scientific conference - Poddar Era; Saha Asim; Mankad Minal (BMC, 2005)
Abstract Background Every individual mode of health education has its own merits, drawbacks as well as their own sphere of effectiveness. A specific mode of communication is more useful in a specific setting on a specific group than others. To search for optimum mode of communication for a specific audience is a major area of research in health education. The issue of imparting health education to a gathering of educated people, representing different fields of knowledge has remained a relatively less lighted aspect of health education research. In this backdrop this study was initiated for making a comparative assessment of different methods of dissemination of health education among educated people. Methods A cross-sectional interviewer administered questionnaire survey was conducted involving 142 randomly selected subjects during the last session of a five-day conference having health as main theme when the opinion of the delegates regarding different communication methods was asked for. Collected data was analyzed not only to find out the optimum mode of education dissemination in such a setting but also to find the contribution of different factors in the preferences of the study subjects. Results The participants opted more (60%) for focused programs of smaller audience (sectional program). In both broad area (main program) and focused area programs (sectional), the participants preferred lectures (62% and 65.7% respectively). Specific topics were preferred both in lectures (67.6%) and symposia (57.7%). In the exhibition, exhibits seemed to be more attractive (62%) than the posters. Qualification has emerged to be a contributing factor in peoples' choice towards sectional programme and also in their affinity to symposia. Increased age was a significant contributor in participants' preference towards specific topics. Physical barriers of communication appeared to be a problem in the main program as well as in the exhibition. Lack of coherence among the speakers was reported (69%) to be a major reason for which symposia was not preferred. Conclusion This study concluded that while planning for health education dissemination in an educated group a focused programme should be formulated in small groups preferably in the form of lectures on specific topics, more so while dealing with participants of higher age group having higher educational qualification.